Trigonal-Sparing vs. Trigonal-Involved OnabotulinumtoxinA Injection for the Treatment of Overactive Bladder: A Systematic Review and Meta-Analysis - Cui, Yuanshan; Cai, Tong; Dong, Tiantian; Zhang, Xiaoyi; Zhou, Zhongbao; Lu, Youyi; Zhang, Yong; Wu, Jitao; Gao, Zhenli; Wang, Yongqiang; Dong, Liying (Frontiers in Neurology, 2021)
Objective: Overactive bladder (OAB) is a disease characterized by the presence of urinary urgency. We carried out a meta-analysis to assess the effectiveness and safety of trigonal-involved injection of onabotulinumtoxinA (BoNT-A) in comparison with the trigonal-sparing technique in cases with OAB (neurogenic detrusor overactivity (NDO) and idiopathic detrusor overactivity (IDO)). Methods: Randomized controlled trials (RCTs) of BoNT-A injection for OAB were searched systematically by using EMBASE, MEDLINE, and the Cochrane Controlled Trials Register. The datum was calculated by RevMan version 5.3.0. The original references of relating articles were also reviewed. Results: Six RCTs involving 437 patients were included in our analysis. For OAB, the trigone-including group showed different in patient symptom score (p=0.03), complete dryness rate (p=0.002), frequency of incontinence episodes (p=0.01), detrusor pressure at maximum flow rate (p=0.01), volume at the first desire to void (p=0.0004) compared with trigone-sparing group. Also, trigone-including intradetrusor injection demonstrated significantly improvement in patient symptom score(p=0.0004), complete dryness rate (p=0.0002), frequency of incontinence episodes (p=0.0003), detrusor pressure at maximum flow rate (p=0.01), volume at the first desire to void (p=0.00006) compared with the trigone-sparing group for treatment of NDO. The adverse events rates were similar in both groups. Conclusions: The meta-analysis has demonstrated that trigone-including BoNT-A injection was more effective compared with the trigone-sparing injection for the treatment of OAB, especially for NDO.